PEMANFAATAN PLATFOM CANVA SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI ERA DIGITAL DI SEKOLAH MENENGAH PERTAMA KATOLIK SANTA MARIA 2 MALANG - Anisa Putri Anggraini; Didik Iswahyudi; Yulius Rustan Effendi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the utilization of the Canva platform as a learning medium in Civic Education (PPKn) learning to improve students’ learning motivation in the digital era at SMP Katolik Santa Maria 2 Malang. This research employed a qualitative approach with a case study design. Data were collected through observations, semi-structured interviews, and documentation involving the principal, vice principal of curriculum, Civic Education teachers, ICT teachers, and eighth-grade students. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that the use of Canva in learning activities increased students’ motivation, focus, participation, and understanding of the material. Canva helped teachers present learning materials in a more visual, interactive, and contextual manner through presentations, infographics, posters, and project-based assignments. Students became more enthusiastic, active in discussions, and confident in expressing their ideas during the learning process. In addition, Canva supported collaborative learning and strengthened students’ digital literacy skills. However, several obstacles were found, such as internet connectivity issues and differences in students’ digital abilities. Teachers addressed these challenges by providing guidance, selecting simple features, and combining Canva with other learning methods. Overall, Canva proved to be an effective digital learning medium that supports innovative, interactive, and student-centered Civic Education learning in the digital era.